Agency in avoidant personality disorder: a narrative review - Weme, Andrea Varga; Sørensen, Kristine Dahl; Binder, Per-Einar (Frontiers in Psychology, 2023)
Objectives: Avoidant personality disorder (AvPD) is a highly prevalent personality disorder, especially in clinical settings, yet scarcely researched. People diagnosed with AvPD have severe impairments in functioning and suffer greatly, yet we still lack meta-analytic evidence for therapy and only a few RCTs are conducted. Patient factors are the most important for outcome in therapy, in general. . Lack of agency might be a core deficit in people diagnosed with AvPD. Their conditions might be improved if we understand their agency better. We review previous research regarding psychological mechanisms and interpersonal relationships that facilitate or hinder agency in AvPD in daily life and psychotherapy. Methods: Summarizing original literature in a narrative review with reflexive thematic analysis. Results: People diagnosed with AvPD seem to have significant impairments in their sense of agency due to a lack of emotional awareness, an overweight of inhibiting vs activating emotions, and difficulties regulating emotions. Difficulties also seem related to high levels of attachment avoidance and fear, creating strong ambivalence in social needs, in addition to a strong tendency to subordinate to others. A weak sense of self with a poor narrative, self-doubt, and harsh self-critique makes a reflexive and intentional stand increasingly difficult for these people. Conclusions: This review gives a clinically meaningful understanding of core strengths and deficits in the personality functioning of AvPD that can help clinicians map out important therapeutic work, identify barriers to client-agency in therapy, and work through relational difficulties in the therapeutic alliance.